2010
DOI: 10.1073/pnas.0912105107
|View full text |Cite
|
Sign up to set email alerts
|

Pantethine rescues a Drosophila model for pantothenate kinase–associated neurodegeneration

Abstract: Pantothenate kinase-associated neurodegeneration (PKAN), a progressive neurodegenerative disorder, is associated with impairment of pantothenate kinase function. Pantothenate kinase is the first enzyme required for de novo synthesis of CoA, an essential metabolic cofactor. The pathophysiology of PKAN is not understood, and there is no cure to halt or reverse the symptoms of this devastating disease. Recently, we and others presented a PKAN Drosophila model, and we demonstrated that impaired function of pantoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
166
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(178 citation statements)
references
References 29 publications
11
166
1
Order By: Relevance
“…Previously, it was demonstrated that CSE deficiency is linked to increased levels of oxidative stress (42). As a readout for oxidative stress, we used OxyBlot analysis as previously described (43). SCA3 flies showed increased levels of oxidized proteins (characteristically visible as multiple bands) compared with their isogenic non-SCA3 control lines (Figures 4C, D).…”
Section: Overexpression Of Cse Reduces Levels Of Oxidative Damage Of mentioning
confidence: 99%
“…Previously, it was demonstrated that CSE deficiency is linked to increased levels of oxidative stress (42). As a readout for oxidative stress, we used OxyBlot analysis as previously described (43). SCA3 flies showed increased levels of oxidized proteins (characteristically visible as multiple bands) compared with their isogenic non-SCA3 control lines (Figures 4C, D).…”
Section: Overexpression Of Cse Reduces Levels Of Oxidative Damage Of mentioning
confidence: 99%
“…As an additional dietary approach, we tested whether adding cysteine to pantothenate could improve any HS-induced Because steady-state levels of metabolites do not refl ect the metabolic fl ux through that pathway, we took a functional approach to test whether the conversion of pantothenate to CoA was important for tolerance of HS diets. We targeted two enzymes that catalyze CoA synthesis from pantothenate, the rate-limiting pantothenate kinase ( PK also known as fumble , CG5725 ) and phosphopantothenoylcysteine synthase ( PPCS , CG5629 ), which, like fumble , is required for growth of Drosophila S2 cells ( 31 ). Because the FB is the primary site of TG synthesis in the fl y, we used FB-specifi c RNAi to reduce CoA biosynthesis from pantothenate by targeting PK/fumble and PPCS in this tissue ( Fig.…”
mentioning
confidence: 99%
“…In samples of rat livers, d-pantethine was shown to be more efficient than d-PaA in inducing the synthesis of CoA, but d-pantethine failed to affect the mitochondrial CoA contents if added to isolated mitochondria (8). Rana et al (9) reported that d-pantethine rescued pantothenate kinase-associated neurodegeneration in Drosophilia. These reports (6)(7)(8)(9) suggest that the efficacy of d-pantethine as a CoA precursor is dependent upon the particular organism and imply that d-pantethine may be a precursor of CoA as well as d-PaA in mammals.…”
mentioning
confidence: 99%
“…Rana et al (9) reported that d-pantethine rescued pantothenate kinase-associated neurodegeneration in Drosophilia. These reports (6)(7)(8)(9) suggest that the efficacy of d-pantethine as a CoA precursor is dependent upon the particular organism and imply that d-pantethine may be a precursor of CoA as well as d-PaA in mammals. The synthetic pathway could be: d-pantethine→d-pantetheine→ 4′-phosphopantetheine→dephospho-CoA→CoA and/or d-pantethine→d-pantetheine→d-PaA→4′-phosphopantothenic acid→4′-phosphopantothenylcysteine→4′-phosphopantetheine→dephospho-CoA→CoA.…”
mentioning
confidence: 99%